L’innesto della peste. Ovvero, il comico in tempi di calamità - Giancarlo Alfano (Laboratoire Italien)
This essay aims to interpret the narrative construction of the Decameron as an experience of shared inoculation of evil. By examining the specific case of comedy (understood as a thematic repertoire and as a coherent stylistic register), Boccaccio’s theoretical declarations are addressed and cross-referenced with concrete textual strategies in order to emphasise the moral character of the work and more specifically as a representation of the possibility of achieving –in the words of the Italian philosopher Roberto Esposito– “common immunity” by sharing “comic evil” inoculation strategies to come through the plague unscathed and so reconquer the world.